PENGARUH PENDUDUK, PDRB PERKAPITA DAN HOTEL TERHADAP PENERIMAAN PAJAK DAERAH KABUPATEN/KOTA DI SUMATERA BARAT - Putri, Tomo Pramana; Alianis, Alianis (Universitas Negeri Padang, 2020)
Abstract : This study aims to analyze the effect of population, GDP per capita and hotelson local tax revenues in districts / cities in West Sumatra. The data used are secondarydata in the form of panel regression in 19 districts / cities in West Sumatra province. Thesource of this data is the West Sumatra Central Statistics Agency (BPS). The variablesused in this study are population (X1), GDP per capita (X2) and hotels (X3). Themethods used in this research are: (1) Panel Regression Model (2) Classical AssumptionTest (3) t test (4) f test. The results of this study indicate that (1) total population has anegative and significant effect on local tax revenues in regencies / cities in WestSumatra. (2) PDRB Per capita has a positive and significant effect on local tax revenuesin districts / cities in West Sumatra. (3) The number of hotels has a positive andsignificant effect on local tax revenues in districts / cities in West Sumatra.Keywords: Tax Revenue, Population, PDRB Per capita, Hotel.